2020
DOI: 10.1055/s-0040-1713802
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Preoperative Endometrial Histopathological Sampling as a Predictor of Final Surgical Pathology in Endometrial Cancer

Abstract: Objective To evaluate the agreement between the histopathological diagnoses of preoperative endometrial samples and surgical specimens and correlate the agreement between the diagnoses with the impact on surgical management and the survival of patients with endometrial adenocarcinomas. Methods Sixty-two patients treated for endometrial cancer at a university hospital from 2002 to 2011 were retrospectively evaluated. The histopathological findings of preoperative endometrial samples and of surgical sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
2
4
0
3
Order By: Relevance
“…Similar results were found in the research of Piotto et al. ( 28 ), which showed that the general consistency between preoperative endometrial specimens and surgical specimens was 46.8% (kappa: 0.279, P < 0.001), and the agreement varied significantly by tumor type and grade (endometrioid adenocarcinoma grade 1, 64.0%; and grade 2, 50.0%; and non-endometrioid adenocarcinoma, 81.8%). A meta-analysis involving 45 studies found that the pooled agreement rate between preoperative endometrial sampling and final diagnosis for tumor grade was 0.67 (95% CI, 0.60–0.75), and Cohen’s k was 0.45 (95% CI 0.34–0.55).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar results were found in the research of Piotto et al. ( 28 ), which showed that the general consistency between preoperative endometrial specimens and surgical specimens was 46.8% (kappa: 0.279, P < 0.001), and the agreement varied significantly by tumor type and grade (endometrioid adenocarcinoma grade 1, 64.0%; and grade 2, 50.0%; and non-endometrioid adenocarcinoma, 81.8%). A meta-analysis involving 45 studies found that the pooled agreement rate between preoperative endometrial sampling and final diagnosis for tumor grade was 0.67 (95% CI, 0.60–0.75), and Cohen’s k was 0.45 (95% CI 0.34–0.55).…”
Section: Discussionsupporting
confidence: 90%
“…The study of Batista et al (27) showed that the overall concordance of preoperative histological examination for final surgical pathology grading in EC was 60.75% to 67.24% for G1, 43.75% for G2, and 40% for G3 tumors, which indicated that preoperative endometrial sampling was only a modest predictor of postoperative histological grading. Similar results were found in the research of Piotto et al (28), which showed that the general consistency between preoperative endometrial specimens and surgical specimens was 46.8% (kappa: 0.279, P <0.001), and the agreement varied significantly by tumor type and grade (endometrioid adenocarcinoma grade 1, 64.0%; and grade 2, 50.0%; and non-endometrioid adenocarcinoma, 81.8%). A metaanalysis involving 45 studies found that the pooled agreement rate between preoperative endometrial sampling and final diagnosis for tumor grade was 0.67 (95% CI, 0.60-0.75), and Cohen's k was 0.45 (95% CI 0.34-0.55).…”
Section: Discussionsupporting
confidence: 89%
“…O câncer de endométrio é a segunda doença maligna ginecológica mais comum, sendo a sexta causa mais comum de morte por neoplasias no sexo feminino 1 . No Brasil, 6540 novos casos foram estimados para o ano de 2020 2 .…”
Section: Introductionunclassified
“…Quando diagnosticado em estágio inicial, esse tipo de neoplasia tem uma sobrevida após 5 anos de 90%, mas em caso de diagnóstico tardio, essa taxa pode cair para até 30%, o que justifica a importância do rastreamento e diagnóstico precoce, tanto do câncer de endométrio em si quanto das suas lesões pré-malignas, como hiperplasia com atipia 1,4 . Dentre a propedêutica disponível para o rastreamento de lesões ginecológicas, a ultrassonografia transvaginal (USTV) é um exame acessível, não invasivo e de boa acurácia e, por isso, frequentemente solicitado por ginecologistas e obstetras.…”
Section: Introductionunclassified
See 1 more Smart Citation